2015
DOI: 10.4088/jcp.14m09435
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Correlates of <em>DSM-5</em> Attenuated Psychosis Syndrome in a Sample of Adolescent Inpatients With Nonpsychotic Psychiatric Disorders

Abstract: ClinicalTrials.gov identifier: NCT01383915.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 0 publications
4
29
1
1
Order By: Relevance
“…Contrary to brain morphological abnormalities observed in adults at CHR-P (Harrisberger et al, 2016;Walter et al, 2016), structural alterations have not been robustly confirmed in adolescents at CHR-P (Ziermans et al, 2009). These differences may reflect different maturational ages of the brain across these two populations or may alternatively be due to a lower true-positive rate for psychosis in paediatric CHR-P samples due to more nonspecific and overlapping phenomenologies of concurrently emerging psychiatric disorders (Gerstenberg et al, 2015(Gerstenberg et al, , 2016Kelleher et al, 2012;Schimmelmann, Michel, Martz-Irngartinger, Linder, & Schultze-Lutter, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to brain morphological abnormalities observed in adults at CHR-P (Harrisberger et al, 2016;Walter et al, 2016), structural alterations have not been robustly confirmed in adolescents at CHR-P (Ziermans et al, 2009). These differences may reflect different maturational ages of the brain across these two populations or may alternatively be due to a lower true-positive rate for psychosis in paediatric CHR-P samples due to more nonspecific and overlapping phenomenologies of concurrently emerging psychiatric disorders (Gerstenberg et al, 2015(Gerstenberg et al, , 2016Kelleher et al, 2012;Schimmelmann, Michel, Martz-Irngartinger, Linder, & Schultze-Lutter, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical comorbidity in the CHR-P state. Systematic review: Six studies had a primary focus on the investigation of comorbidities in CHR-P (Gerstenberg et al, 2015;Kline et al, 2016;Morelli et al, 2019; Pelizza, Poletti, et al, 2019;Pitzianti et al, 2019;Stain et al, 2018). Comorbidity was frequent (from 46.4% to 7%) in adolescents at CHR-P (Table S7).…”
Section: Meta-analysismentioning
confidence: 99%
“…While most reports to date on APS are based on cohorts that also include adults (25,(28)(29)(30), APS features often occur for the first time in adolescence (31,32). Broadly speaking, studies that focus on DSM-5-APS in adolescents are scarce (21,22), and there are few studies on APS in adolescents in clinical care and hospital settings.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only a few efforts have been made (22,33,34) to characterize APS, excluding other ultra-high risk criteria, and advance knowledge specifically in children and adolescents, comparing them to other help-seeking individuals. Among them, 22 APS individuals were compared to other treatment-seeking individuals and healthy controls regarding clinical and cognitive features (34), finding that APS was associated with impaired neurocognition.…”
Section: Introductionmentioning
confidence: 99%
“…This area of conflict is influenced by many different and important factors, among others, by clinicians' uncertainties about the validity of the CHR state in people with highly complex symptom combinations, mostly multiple comorbid psychiatric disorders, additional biological and environmental risk factors, and often frequent childhood adversities. In fact, several recent studies suggest that at least the psychosis CHR criteria may affect a higher proportion of adolescents than adults, with emergence of CHR criteria-based symptomatology at the same time as other mental disorders emerge, complicating the clinical picture [140][141][142]. Furthermore, in a program focusing predominantly on adolescents, younger age of onset of CHR criteria within adolescence was associated with lower conversion rates to psychosis [21].…”
mentioning
confidence: 99%